Readiness for Training Disabled Students in Academic Staff of Universities - Sorokin N.Y; Lukovenko T.G (Moscow State University of Psychology and Education, 2018)
The readiness of the teaching staff of higher educational institutions for teaching and psychological and pedagogical support of students with disabilities is being considered. We emphasize that the personnel of the educational organization need special competence to work with persons with disabilities of various nosological groups. The issues of creating an accessible environment in the university were studied, the readiness of teachers to apply special educational technologies in the training of students with disabilities, to develop teaching and methodological materials; the ability to establish pedagogically appropriate relationships with students, and provide psychological and pedagogical support in matters of personal and professional self-determination. The results show a high degree of importance of special professional competencies for inclusive education. But, at the same time, teachers assess their own level of preparedness with students with disabilities as insufficient, which allowed to determine the main areas of work.